Assessing the Impact of No-Tillage Duration on Soil Aggregate Size Distribution, Stability and Aggregate Associated Organic Carbon - Kopano Conferance Phefadu; Lawrence Munjonji (Agronomy)
Soil aggregation results from the rearrangement, flocculation and cementation of primary soil particles. Furthermore, the aggregates undergo transformation under no-tillage (NT) overtime. Soil organic carbon (OC) is the major component of soil organic matter and is protected within aggregates and can serve as a proxy for soil structural stability. Organic matter contributes significantly to the formation of soil aggregates and the carbon within them is protected against degradation. This study assessed the impact of tillage systems, soil depth and no-till duration on soil aggregate size distribution, stability and aggregate associated carbon. It was carried out in Thohoyandou (Tshivhilwi and Dzingahe), Vhembe district, Limpopo province, South Africa. The soil samples were collected from NT, conventional tillage (CT) and virgin (VG) fields in the topsoil (0–30 cm) and subsoil (30–60 cm) at each location. The duration of NT for fields in Tshivhilwi and Dzingahe were 8 years (short-term) and >40 years (long-term), respectively. The results showed that macro-aggregates constituted the largest proportion of aggregates, with a percentage contribution of >60% during the short-term and long-term. The mean weight diameter (MWD) varied significantly between NT and VG in the subsoil for the short-term NT. The aggregates were more stable in the short-term NT than long-term NT. Organic carbon in all aggregate fractions between the tillage systems in the topsoil was not significantly affected after more than 40 years. The MWD was higher in the subsoil than topsoil in NT and CT during both periods. Micro-aggregates contained greater OC than other fractions. The study showed that the impact of NT on aggregation, structural stability and the capacity to store carbon vary overtime. It is recommended that the aggregation and/or structural stability of different soil textures under NT with different cropping systems and management practices should be studied periodically.